Review of G. E. Romero, Javier Pérez-Jara and Lino Camprubí, eds., Contemporary Materialism: Its Ontology and Epistemology, Synthese Library, 447, Springer, 2022. - PEDRO SANTANA MARTÍNEZ (Manuscrito)
Abstract It is a review of G. E. Romero, Javier Pérez-Jara and Lino Camprubí, eds., Contemporary Materialism: Its Ontology and Epistemology, Synthese Library, 447, Springer, 2022,